Merchants of knowledge: Petty retail and differentiation without consolidation among farmers in Maharashtra, India. (19th January 2018) - Aga, Aniket
Abstract: This article focuses on the intermediary figure of the village‐level petty retailer of chemical inputs, providing an account of the everyday relationships of farmers with transnational and domestic agribusiness capital. Retailers are figures from whom farmers purchase seeds, fertilizers, pesticides, and other chemicals. The article traces the rise of village‐level retailers in western Maharashtra, India, since the 1990s, and finds that Maratha (a dominant landholding cultivator caste) households have ventured into retailing. Further, farmers depend on retailers for credit, technical knowledge, and for the sale of their harvest. By analysing the pressures and risks of petty retail, visible in interactions with farmers, the article argues that even as retailing provides avenues for upward mobility to petty agricultural commodity producers, the trade is too volatile for the gains to sustain. Thus, the entry of Marathas into petty retail is akin to an attempt at class differentiation but without consolidation.